AB1089 Introducing Vascular Ultrasound in the Diagnosis of Giant Cell Arteritis in Denmark. (9th June 2015) - Chrysidis, S.; Døhn, U.M.; Fredberg, U.; Lorenzen, T.; Terslev, L.; Diamantopoulos, A.P.
Abstract : Background: There is an increasing use of vascular ultrasound (US) as a diagnostic tool in Giant Cell Arteritis (GCA) internationally. Therefore, it is of great importance to develop and standardise examination technique, machine settings and offer proper training of ultrasonograhers to ensure a high level of expertise in order to obtain reliable results Objectives: The aim of this study is to evaluate a specific vascular US training program in GCA diagnostic. Methods: Patients suspected for GCA were US evaluated by five rheumatologists with long-standing experience in musculoskeletal US who were trained by the following program: Participation at the International Workshop on ultrasound in Large Vessel Vasculitis & Polymyalgia Rheumatica in Kristiansand, Norway (5 hours theoretical and 10 hours supervised hands-on education). Later, further training and standardisation was obtained at a two days workshop (Esbjerg, Denmark) including training with both healthy persons and GCA patients (totally 6 hours of supervised hands-on trainings and 1 hour of image evaluation). High-end equipment (Hitachi Preirus & GE logic-9E), with comparable settings and standardized examinations methods was used. As part of an ongoing study the following arteries were evaluated bilaterally: temporal artery (common, pariental and frontal branch)(AT), the facial artery (AF), the common carotid artery (AC)and the axillary artery (AA). Both still images in two planes and films were recorded. Images were subsequently evaluated first by the performing ultrasonographer and after by a blinded external expert (gold standard). Detailed feedback on the US technique was given to the performing ultrasonographer by the external expert. US was considered positive when a homogeneous hypoechoic thickness >1.5 mm in AC and >1mm in AA, in transverse and longitudinal view was observed. For the AT and AF, the halo sign (hypoechoic arterial wall swelling in transverse and longitudinal view) and/or positive compression-sign (impaired compression) was considered a sign of vasculitis Results: Twenty patients suspected for GCA were enrolled in a period of 8 months in 3 Danish centres (Esbjerg, Glostrup, Silkeborg) In all ten patients with positive Temporalis Artery Biopsy (TAB) was found US vasculitis in AT according to both external expert and performing ultrasonographer. Arteritis in AA was found in 3/10 according to external expert and in 4/10 patients according to performing ultrasonographer In the rest 10 patients with negative TAB were no sign of US vasculitis in AT and AF (external expert) and according to performing ultrasonographer there was US AT vasculitis in 1/10. Arteritis in the extracranial arteries was found in 2 patients (bilateral in AA) according to both expert and ultrasonographer. Totally, 240 vessels were scanned and vasculitis changes were observed in 58 vessels (expert) and in 55 vessels (performing ultrasonographer). The inter-observer agreement between the performing ultrasonographer and the blinded expert was excellent in all 3 centre (table ) Cohens kappa-coefficient Esbjerg k=0, 89, Glostrup k=0, 91 & Silkeborg k=0, 82. Conclusions: The above mentioned educational program showed excellent results in diagnostic of GCA and excellent interobserver agreement. It could be considered as a teaching model to vascular ultrasound in the diagnosis of GCA Disclosure of Interest: None declared